Frequency of Ki-67 (MIB-1) and P53 expressions among patients with prostate cancer - Seyed Hamid Madani; Somayeh Ameli; Sedigheh Khazaei; Malek Kanani; Babak Izadi (Wolters Kluwer Medknow Publications, 2011)
Context: Prostate cancer is the most common malignant tumor in men. Tumor grade is one of the most important prognostic factors of prostate cancer. P53 and Ki-67 expressions have also been considered to be prognostic factors. Aims: This study was performed to investigate the frequency of these proteins expression and compare the obtained results with Gleason's grading. Settings and Design: In this cross-sectional study, 49 paraffin blocks of prostate cancers were assessed. Tumor grade was determined according to the Gleason's criteria. Materials and Methods: Ki-67 and P53 expressions were determined by immunohistochemical staining. Statistical Analysis: The obtained results were analyzed and evaluated using Spearman's statistical test (SPSS version 15). Results: Three out of 49 (6.1%) cases were well differentiated, 21 (43%) moderately differentiated and 25 (51%) were poorly differentiated. P53 was negative in all well-differentiated cases. Ki-67 was negative in 14 cases (28%) including all well-differentiated tumors. Among moderately and poorly differentiated tumors Ki-67 was negative in eight (38%) and three (12%) of cases, respectively. A statistically significant relation was observed between the increased Ki-67 labeling index (LI) and increased Gleason's grade. Conversely, no statistically significant relation was found between P53 expression and increased Gleason's grade. Conclusions: According to the findings of this study, it seems that Ki-67 can be used as a prognostic factor for prostate cancer. On the other hand, the probable relation between P-53 and prostate cancer prognosis requires further studies.